Nanodiamonds from coal under ambient conditions. Issue 14 (16th March 2015) - Xiao, J.; Liu, P.; Yang, G. W.
Abstract : Nanodiamonds with a cubic phase and a mean size of 3 nm are synthesized from various types of coal at atmospheric pressure and room temperature using a novel process involving laser ablation in liquid. Abstract : Coal is the most abundant energy resource, but it is only useful for producing energy via combustion due to its structural characteristics. However, coal is also inexpensive and is the most plentiful and readily available carbon source material for the production of nanodiamonds compared with the most widely used solid carbon source, high-purity graphite, and the high-purity hydrocarbon gas precursor, methane. Here, we report a simple and green top-down strategy for synthesizing nanodiamonds with a cubic phase and a mean size of 3 nm from various types of coal at atmospheric pressure and room temperature using a novel process involving laser ablation in liquid. Furthermore, we have systematically studied the process of phase transformation from coal to nanodiamonds using nucleation thermodynamics, growth kinetics and structural stability. The synthesized nanodiamonds have turned out to be soluble monodisperse colloids that exhibit strong and stable fluorescence both in alcohol and in water. These results provide a route for producing nanodiamonds from inexpensive and abundant coal.